Arbitraje inversionista-Estado y fragmentación interpretativa de estándares de protección: los casos América Móvil y Telefónica contra Colombia - Lorenzoni-Escobar, Lina (2025)
This article addresses the problematic phenomenon of interpretative fragmentation of clauses in foreign investment protection treaties by international arbitration tribunals, using as a case study the recent awards of América Móvil and Telefónica against Colombia. It is observed how the same facts, decided under different treaties, give rise to dissimilar interpretations of principles as important to state sovereignty as judicial deference, and how, in the face of a much-discussed and questioned standard such as fair and equitable treatment, the tribunal in the Telefónica case decided without providing reasons for its decision, with flawed approaches from the discipline of international law. The article concludes with the importance of the arbitrators’ profile in order to avoid interpretative fragmentation, in reality diagnosing a long-standing problem that is still very much alive.